Understanding peer support among healthcare assistants delivering hospice care at home: a protocol for a realist review - Sonja McIlfatrick; Felicity Hasson; Tracey McConnell; Katarzyna Anna Patynowska (BMJ Open)
Introduction Globally, the demand for community palliative care, delivered within the home setting, is rising. Hospice support workers, also referred to as healthcare assistants, play a crucial role in providing this care, but evidence indicates they face challenges relating to inadequate training, isolation and emotional labour. This realist review aims to understand how peer support interventions can support healthcare assistants in delivering hospice care at home.Methods and analysis The realist review will follow a five-step process to explore the research question: (1) locating existing initial programme theories, (2) searching for evidence, (3) selecting and appraising evidence, (4) extracting and organising data and (5) synthesising evidence and drawing conclusions. Comprehensive searches of academic databases (CINAHL, MEDLINE, AMED, Scopus) and grey literature sources will be conducted between November and December 2024, with no restrictions on publication date applied. Search strategies will be iteratively refined, with evidence selected based on relevance and rigour. Data will be extracted and coded using a realist logic model of analysis. The review will develop an explanatory programme theory for peer-to-peer interventions which would identify what, how, for whom, why and in what circumstances peer-to-peer interventions may support delivery of hospice care at home. It will explore the contexts, mechanisms and outcomes of these interventions using context-mechanism-outcome configurations.Ethics and dissemination Ethical approval is not required as the review involves no primary data collection. This review aims to clarify research gaps, inform next stages of a wider study, policy and practice. Reporting of the findings will adhere to RAMESES publication standards for realist syntheses, ensuring transparency and rigour in reporting. Results will be disseminated through peer-reviewed publications, conference presentations and other strategies identified by the stakeholder group.PROSPERO registration number CRD42024606133.